Strategies for Catchment Development Master Plan and Economic Aspects of Water Resource Planning - Sivakumar, S. (International Journal of Scientific and Research Publications, 2014)
The economic aspects of water resource planning involve the evaluation so far, as practicable in monetary terms of the physical potentialities of the catchment for alternate courses of action involving types of uses, different configurations and sequences of development in time. Interpretation in terms of monetary values of the consequences of alternate courses of action, though most convenient way for comparison, is not always possible since extra market consequences, indirect benefits also become important influences in deciding the project acceptability. This is so because in a welfare economy, economic efficiency measured in terms of market value of what the economy produces is an imperfect measure of economic welfare. The measurement of benefits and costs of development programmes should extend beyond mere market values. This article deals with how these are to be addressed in terms of economic point of view and give some thoughtful contents as guidelines for the preparation of water resource catchment development master plan taking into account the needs of not only irrigated agriculture, but also the various other water uses so that the available water can be put to optimum use.
Keywords: Irrigated agriculture